Investigating the Mediating Role of Self-Compassion in the Relationship Between Narcissism and Academic Self-Efficacy of Final Year Students - Elahe Jafari; Nooshin Taghinejad; Azita AmirFakhraei (Iranian Journal of Educational Research, 2025)
Objective: The present study was conducted with the aim of investigating the mediating role of self-compassion in the relationship between narcissism and academic self-efficacy of final year students. Methods: The methodological framework employed for this descriptive study was correlational in nature, specifically utilizing structural equation modeling. The statistical population pertinent to this inquiry encompasses all final year students enrolled at Bandar Abbas Islamic Azad University (both undergraduate and graduate levels) during the academic year 2024. In this study, sampling was executed via a stratified random sampling technique. The instruments utilized for data collection included Owen and Froman's academic self-efficacy scale (1988), Neff et al.'s self-compassion scale (2003), and Ames et al.'s narcissistic personality scale (2006). Structural equation modeling was employed to evaluate the research hypothesis. Moreover, the software utilized for this analysis was SPSS version 26 and Amos. Results: The outcomes of the statistical analysis indicated that the structural model pertaining to the mediating role of self-compassion in the relationship between narcissism and academic self-efficacy among final year students demonstrated a satisfactory fit. Conclusions: Consequently, it can be posited that students exhibiting a favorable degree of narcissism are likely to experience enhanced academic self-efficacy attributable to the presence of self-compassion.